2019
DOI: 10.1021/acsabm.8b00698
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Physically Cross-Linked F127−α-CD Hydrogels: Preparation, Sol–Gel Transformation, and Controlled Release of 5-Fluorouracil

Abstract: Pluronic F127 is a thermosensitive polymer that has been extensively studied and utilized in biomedicine. To improve the gelation properties of F127, α-cyclodextrin was introduced by physical interactions, such as forming inclusion complexes, hydrogen bond self-assembly, and hydrophobic interactions, to prepare F127−α-CD hydrogels. This study explored the temperature-dependent sol−gel transition behavior, gelation mechanism, interior morphology, and controlled release of the anticancer drug 5-fluorouracil. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Among the stacked-like structures, some aggregation zones were found (yellow arrows). According to Peihong’s study [ 23 ], we could assume that the aggregation zone consists of a firmed 3D structure formed by α-CD/mPEG and α-CD/PEO by the host-guest reaction. In addition, we observed that GEL-CP has a more complex internal structure than GEL-F through the FE-SEM image.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the stacked-like structures, some aggregation zones were found (yellow arrows). According to Peihong’s study [ 23 ], we could assume that the aggregation zone consists of a firmed 3D structure formed by α-CD/mPEG and α-CD/PEO by the host-guest reaction. In addition, we observed that GEL-CP has a more complex internal structure than GEL-F through the FE-SEM image.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies, hydrogel physical properties can be determined by the concentration of α-CD, which is due to the higher concentration of α-CD acting as a host molecule, increased entrapment with guest molecules, and more crosslinking sites. In particular, F127 is actively used as a temperature-sensitive hydrogel, but there has been interest in its high utilization as a host-guest reactive hydrogel using α-CD [ 23 ]. In our study, F127-α-CD was formed under conditions similar to existing research, and the release of BSA protein showed similar patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a major disadvantage for employment in biomedicine, and consequently, significant research effort has been devoted to work around this problem. Approaches include the chemical modification and/or chemical cross‐linking of Pluronics, chain extension to form multiblock poly(ethylene oxide)‐poly(propylene oxide) (PEO‐PPO) polymers, or the generation of blends with other polymers . Epoxides with longer alkyl side chains have also been employed for a similar purpose .…”
Section: Introductionmentioning
confidence: 99%
“… The employment of high molar mass polymer with long, terminal PPO‐blocks was expected to result in a significant increase of the mechanical strength of the corresponding hydrogel. At the same time these chemically conservative manipulations are proposed not to infringe on the very beneficial biocompatibility generally observed for Pluronics, supposedly in contrast to the more drastic changes imparted by other approaches to improve mechanical properties, such as using chemically different monomers or chemical cross‐links . Nonetheless, it has been demonstrated that small changes to the Pluronic structure can have a sizable impact on applicability in biomedicine, so the same must be expected for “reverse Pluronics.”…”
Section: Introductionmentioning
confidence: 99%